A Case of Reading Teaching on Task-Based Teaching Model in Middle Schools - Liu, Yongmei (Pacific International Journal, 2022)
In April 2022, the Ministry of Education of the People’s Republic of China officially announced the English Curriculum Standards for Compulsory Education (2022 Edition). Since the release of the English Curriculum Standards for Compulsory Education (2011 Edition), the reform of the English curriculum for compulsory education has made remarkable achievements; at the same time, however, there are also some problems that need to be solved urgently. The new curriculum standards should change the teaching of vocabulary and grammar knowledge as the main content, select learning contents around the comprehensive performance of core literacy, design teaching units as a whole, and plan the blueprint of unit education. According to the students’ comprehensive performance and the objectives of the school section, the content should be closely related to the real life, especially the social life and learning life that students are familiar with and meet the characteristics of their physical and mental development. The content selected should reflect the characteristics of the times and social progress, focus on the themes of people and nature. Elements on theme, discourse, language knowledge, cultural knowledge, language skills and learning strategies should be considered when selecting the the teaching content. Ultimately, students are expected to use the knowledge and skills to solve tasks and problems in practice. In terms of middle school English teaching, the author holds that Task-Based Teaching Mode will help teachers to achieve the above goals. Task-Based teaching emphasizes learning by doing, which allows students to interact with teachers, and it also creates a favorable environment for students to learn and internalize. The middle school English teaching goal is to help the students to obtain the basic English knowledge and the ability of using English to communicate through listening,speaking,reading and writing training. As a helpful teaching approach, the Task-Based Teaching Model can be widely used. Based on the English classroom of middle school, this thesis discusses the relationship between Task-Based Teaching Model and the modern English class through analyzing the reading in middle school English class. The paper draws a conclusion that Task-Based Teaching Model is effective in middle school English classroom and it can improve students comprehensive ability to a all-round development level.